The University Endoscopy Unit: The Standard of Care? - Jordan Golubov; Paul C Adams (Canadian Journal of Gastroenterology)
In an attempt to investigate practice patterns of the modern gastrointestinal endoscopy unit, a survey was undertaken in 10 university-affiliated endoscopy units in three Ontario cities. The results showed that there was a wide range of premedications used, a nd that there was variation tn the extent of patient monitoring, the method of endoscope sterilization and the degree of safety precautions. This survey provides information on the 'standard of care' in the university endoscopy unit and provides a framework for discussion for the establishment of guidelines for the modern gastrointestinal endoscopy unit.